Revitalization Supervision Islamic Banking in Enhancement Compliance in Indonesia and Malaysia - Yusmad, Muammar Arafat; Irwansyah, Irwansyah; Marinsah, Syamsul Azizul Bin; Ayyub, Mukhtaram; Muang, Muh. Shadri Kahar (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
This study is indicated with social reality that, following three decades of dual banking system implementation in Indonesia, Islamic banks' operational activities are essentially identical with the operations of conventional banks. The thing that distinguishes is only the Shariah